ANALYSIS OF STUDENTS’ SYSTEMS THINKING COMPETENCY PROFILE ON ECOSYSTEM ISSUES - Baharuddin, Rahmat; Saefudin; Kusnadi (DAS CONFERENCE INTERNATIONAL SERIES, 2025)
Systems thinking competency is one of the key competencies for sustainability. It’s seen as an important competency to support the development of sustainability practices. This research aims to analyze the profile of students’ systems thinking competency on ecosystem issues. The research method used in this study was a quantitative descriptive method. The subjects in this study were 50 tenth-year students at one of the high schools in the City of Bandung. The research instrument used was a test instrument in the form of eight essay questions. The test instrument was developed based on the aspects of systems thinking competency. The instrument used in this study has been declared valid and reliable based on the results of judgement by the experts and the results of test item analysis (R= 0,78). Students’ systems thinking competencies were analyzed and classified into four categories, namely, low, medium, developing, and advanced. The results showed that the students’ systems thinking competencies varied in each aspect. In general, it was concluded that students’ systems thinking competencies were in the moderate category. This shows that students’ systems thinking competencies still need to be improved. Systems thinking competency can be improved through the application of learning strategies that involve analyzing the relationship between components in a system as well as its application in daily life.